Influência de diferentes retentores intra-radiculares frente ao teste de impacto: análise dinâmica não-linear em elementos finitos - Silva, Camila Ferreira (2016)
The main difference of a healthy tooth for endodontically treated tooth is the quantity and quality of the radicular dentine. The rehab of endodontically treated tooth is normally used intraradicular posts of various materials. The objective of this study is to evaluate the biomechanical behavior of e incisor endodontically treated through stress analysis, varying the type of intra-radicular retainer front impact test. A two-dimensional model was generated from a model of a bovine maxillary central incisor endodontically treated and from a intact incisor(II). A non-linear dynamic analysis is used to simulate the impact test, where a rigid object model had achieve a velocity of 1 m/s -1. The image generated show the sites with accumulation and dissipation of tensions on three levels: Teeth restored with cast post an core (CPC), teeth restored with glass fiber post (GFP) and otherwise intact incisor (II). The biomechanical behavior of endodontically treated teeth were analyzed by analysis of concentration and distribution of strain and stress (Von Misses and modified von Misses).The CPC had shown more stress inside the root than GFP. The strain on dentin were higher on CPC model than GFP model, although the strain in the post were bigger at the GFP. None of the models had similar values to the II. It is important to analyze what is the susceptibility of the patient to suffer a frontal impact before making the choice of intraradicular post for the rehabilitation of anterior teeth.